2019
DOI: 10.1177/0003065119847170
|View full text |Cite
|
Sign up to set email alerts
|

Teleanalysis: Slippery Slope or Rich Opportunity?

Abstract: In certain cases, and under certain conditions, extremely useful analytic work can be done on the phone or through videoconferencing. Contrary to what some critics of teleanalysis maintain, with patients who are motivated and can make use of analysis, physical distance between analyst and patient and/or occasional technological difficulties do not limit or preclude successful analysis. Clinical material from three teleanalyses demonstrates various conditions that help make teleanalysis useful. Instead of being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
33
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 48 publications
1
33
0
3
Order By: Relevance
“…A common fear about conducting teleanalysis is that use of the medium will allow the patient (or the patient and therapist together) to descend the slippery slope into an enactment: a need for control over the terms of the session and the desire not to come in (Mirkin 2011), a fear of closeness, a patient’s fear of putting effort into relationships. But, as both Mirkin (2011) and Ehrlich (2019) describe in detail, it appears that this is a problem not so much of medium as of technique: as in any treatment, if therapists can help patients explore the experience of what is happening, and their response to it, they are more likely to find what is happening helpful (Mirkin 2011).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A common fear about conducting teleanalysis is that use of the medium will allow the patient (or the patient and therapist together) to descend the slippery slope into an enactment: a need for control over the terms of the session and the desire not to come in (Mirkin 2011), a fear of closeness, a patient’s fear of putting effort into relationships. But, as both Mirkin (2011) and Ehrlich (2019) describe in detail, it appears that this is a problem not so much of medium as of technique: as in any treatment, if therapists can help patients explore the experience of what is happening, and their response to it, they are more likely to find what is happening helpful (Mirkin 2011).…”
mentioning
confidence: 99%
“…Russell (2015) suggests that therapists conducting teleanalysis tend to avoid considering the meanings of technological events such as disconnections or a grainy image, or other frame issues that occur in teletherapy, due to the “two-dimensionality” of the medium. However, in her critique of Russell’s analysis, Ehrlich (2019) suggests that Russell is interpreting therapists’ reactions simply as reactions to the medium of teletherapy, rather than as transferential/countertransferential reactions to it. Zalusky (1978) describes a range of reactions, such as fear of colleagues’ judgments, guilt about use of a nontraditional medium, and fear of providing substandard treatment; I believe therapists may also fear loss of control of the frame, have intense personal transferences to technology as a separate object, or fear personal constrictions on their bodies, as might occur sitting in front of a screen and needing to remain in view.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among psychodynamic-oriented therapists, there is a continuum of conceptions that varies from those that are pro online treatments to those who are against it, the latter based on the assumptions that psychodynamic process would not developed in this context and that interventions would be limited to support (Ehrlich, 2019). However, its noteworthy, that most of authors that recommend or not the practice of online psychodynamic therapy do so based on their own clinical experience, using clinical vignettes of their own cases, without any systematic measurement (Ehrlich, 2019). Therefore, this conclusion may denote a researcher bias, and not derived from a systematic observation of the real process of treatment (Serralta, Nunes, & Eizirik, 2011).…”
mentioning
confidence: 99%
“…In fact, little is known about the qualitative aspects of online relationship; and there are many controversies, in literature, about whether alliance and other dynamic therapeutic processes would be the same. For example, although some (Carlino, 2011;Ehrlich, 2019) concluded that psychodynamic psychotherapeutic work is not negatively affected by remote relationship, Russel (2015) suggests that, because of the physical distance between the pair and the split created by the computer screen, aggressive and primitive content could not be fully expressed by the patient. Thus, treatment could turn out to be incomplete and/or inefficient.…”
mentioning
confidence: 99%